Table of Content - - (Journal of Arabic Language Sciences and Literature, 2023)
Table of Content:1. A pragmatic study of directive speech acts in the cartoon “Sadaqa Rasoul Allah”Prof. Asem Hehadeh Ali, Prof. Mohammad Ahmad Alqudah, Mrs. Mawaddah Mohd Zaki2. Textual coherence in Surat At-Takwir Through a conscientious referral - A textual studyDr. Hamad Abdullah Hamad Al-Saif3. The semantic orientation of the Qur’anic witness in Mughni al-Labib, between Ibn Hisham and the commentators, Bab al-Ain as a modelDr. Salman Saud Muslim Albalawi4. Calculation of sentences between Arabic and Hebrew, models and comparisonsMr. Salameh Saleem Salameh Oudeh, Dr. Ahmed Hamed, Dr. Adel Shaqour5. The Influence of Followed NounsDr. Bahiya Ahmad Abdullah Daoud, Prof. Mohammad Ali Younos Rabba6. The Village in Al-Ashmawi's Diwan of (The Basil Vendor)Mrs. Mrwa Mokhtar Elgheity7. Parallel text in the Arabic novel (selected models)Mrs. Ahlam Maze Bakri, Co-Prof. Nadir Qasim
Keywords: Journal of Arabic Language and Literature